Angon Rasa in the Perspective of Javanese Culture and Surakarta-Style Karawitan ART - Aldy Pratama; Suyoto Suyoto (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Angon rasa is Javanese culture related to the Karawitan Surakarta style. This study uses a qualitative method by analyzing using literature studies, interview, and conducting field obervations. The method by an analysis usng the concept of garap by Rahayu Supanggah, and concept of rasa by Setiawan Edi Wibowo. The result of study revealed that angon rasa is one of the Javanese culture in the form of management attitudes which are then applied in karawitan. There are several karawitan musical performances in the form of determining the laras and pathet; bawa, andhegan sinden with thinthingan gendèr; and tabuhan gong as a musical accent. Angon rasa will eventually become a musical function that is always needed for its existence in the Surakarta style karawitan and in daily life. This thesis have many value about management attitudes can applicated in daily life and musical show.Among this value are ngerti ing semu tanggap ing sasmita, sambung rapet, and gambuhing rasa.